Beyond the Inquisition : Ambrogio Catarino Politi and the Origins of the Counter-Reformation - Caravale, Giorgio (Book collections on Project MUSE., 2017)
In Beyond the Inquisition, originally published in an Italian in 2007, Giorgio Caravale offers a fresh perspective on sixteenth-century Italian religious history and the religious crisis that swept across Europe during that period. Through an intellectual biography of Ambrogio Catarino Politi (1484-1553), Caravale rethinks the problems resulting from the diffusion of Protestant doctrines in Renaissance Italy and the Catholic opposition to their advance. At the same time, Caravale calls for a new conception of the Counter-Reformation, demonstrating that during the first half of the sixteenth ce.